2021
DOI: 10.18103/mra.v9i4.2356
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing HIV Prevention Services: Exploring Psychosocial Associations of HIV Antibody Testing Frequency among Sexually Active Men who have Sex with Men

Abstract: Despite recommendations of annual HIV testing for high-risk individuals, one-third of infected men who have sex with men (MSM) are unaware of their serostatus. In an effort to improve HIV prevention services and subsequently decrease prevalence, this study aimed to examine the HIV testing patterns and factors associated with testing frequency among MSM. Utilizing eight reliable and validated instruments and a sample of 374 sexually active MSM, this study examined a series of demographic, behavioral and psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(45 reference statements)
1
0
0
Order By: Relevance
“…The results from this study showed that HIV testing knowledge score was associated with having institutional HIV testing after high-risk sexual behavior among MSM, which is in accordance with a US study comprising 374 MSM from Atlanta, indicating that greater HIV knowledge was associated with greater likelihood and frequency of HIV testing [29]. As knowledge is critical in making health decisions, and the knowledge of HIV has been studied and found to be associated with reduced high-risk sexual behaviors among MSM [30], HIV/AIDS interventions including HIV knowledge education are required.…”
Section: Discussionsupporting
confidence: 89%
“…The results from this study showed that HIV testing knowledge score was associated with having institutional HIV testing after high-risk sexual behavior among MSM, which is in accordance with a US study comprising 374 MSM from Atlanta, indicating that greater HIV knowledge was associated with greater likelihood and frequency of HIV testing [29]. As knowledge is critical in making health decisions, and the knowledge of HIV has been studied and found to be associated with reduced high-risk sexual behaviors among MSM [30], HIV/AIDS interventions including HIV knowledge education are required.…”
Section: Discussionsupporting
confidence: 89%